2017
DOI: 10.1007/s12010-017-2639-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Genome and Chromium Metabolism-Related Genes of Serratia sp. S2

Abstract: This study is to investigate the genome sequence of Serratia sp. S2. The genomic DNA of Serratia sp. S2 was extracted and the sequencing library was constructed. The sequencing was carried out by Illumina 2000 and complete genomic sequences were obtained. Gene function annotation and bioinformatics analysis were performed by comparing with the known databases. The genome size of Serratia sp. S2 was 5,604,115 bp and the G+C content was 57.61%. There were 5373 protein coding genes, and 3732, 3614, and 3942 genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Eslami et al [47] previously reported a 22 Kda AzoR from a halophilic bacterium whereas a 29 KDa AzoR was isolated by Nisar et al [48] from a Staphylococcus sp. Dong et al [49] reported many copies of NAD(P)H-dependent AzoR in Serratia sp. S2.…”
Section: Azor Characterizationmentioning
confidence: 99%
“…Eslami et al [47] previously reported a 22 Kda AzoR from a halophilic bacterium whereas a 29 KDa AzoR was isolated by Nisar et al [48] from a Staphylococcus sp. Dong et al [49] reported many copies of NAD(P)H-dependent AzoR in Serratia sp. S2.…”
Section: Azor Characterizationmentioning
confidence: 99%
“…In recent years, researchers have discovered some bacteria that can remove Cr(VI), including Serratia sp. S2 [3], Bacillus cereus [4], Bacillus licheniformis [5], and Sporosarcina saromensis [6]. Although most studies on Cr(VI) removal by bacteria have focused on strain isolation and cultivation, mechanistic studies on chromium metabolism genes and proteins in bacteria are also being conducted.…”
Section: Introductionmentioning
confidence: 99%
“…S2. Genome sequencing analysis revealed that its genome contains ChrA, ChrB, and ChrT genes and ChrAB gene clusters related to Cr(VI) metabolism [3]. However, these studies lacked comprehensiveness and systematicity, so we wondered if we could use modern omics techniques to combine genomics and proteomics for a multiomics analysis, forming a "DNA-protein" association network to better understand the molecular response mechanism of bacteria under exogenous Cr(VI) stress.…”
Section: Introductionmentioning
confidence: 99%
“…Chromium pollutants can be mutagenic, genotoxic, and carcinogenic in humans (Liu et al, 2015;Huang et al, 2017). Cr 6+ compounds can be easily absorbed by different parts of the human body, such as the skin, digestive tract, and respiratory tract (Dong et al, 2018). In addition, chromium can induce cell DNA damage and gene expression (Alimba et al, 2016;Wang et al, 2016;Karthik et al, 2017).…”
Section: Introductionmentioning
confidence: 99%